1995
DOI: 10.1038/378785a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glycogen synthase kinase-3 by insulin mediated by protein kinase B

Abstract: Glycogen synthase kinase-3 (GSK3) is implicated in the regulation of several physiological processes, including the control of glycogen and protein synthesis by insulin, modulation of the transcription factors AP-1 and CREB, the specification of cell fate in Drosophila and dorsoventral patterning in Xenopus embryos. GSK3 is inhibited by serine phosphorylation in response to insulin or growth factors and in vitro by either MAP kinase-activated protein (MAPKAP) kinase-1 (also known as p90rsk) or p70 ribosomal S6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

149
3,884
12
38

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,738 publications
(4,083 citation statements)
references
References 28 publications
149
3,884
12
38
Order By: Relevance
“…Akt can propagate oncogenic signaling via target proteins with a consensus sequence for Ser/Thr phosphorylation, such as GSK-3b. When GSK-3b is negatively regulated by phosphorylation at Ser9 (Cross et al, 1995), it enhances cell migration via dephosphorylation of focal adhesion kinase (FAK) at Ser722 Bianchi et al, 2005) consistent with our results. Inactivation of PTEN also propagates signaling to proteins further downstream, like S6K on the Akt -Tsc1/2 -mTor -S6K axis.…”
Section: Discussionsupporting
confidence: 91%
“…Akt can propagate oncogenic signaling via target proteins with a consensus sequence for Ser/Thr phosphorylation, such as GSK-3b. When GSK-3b is negatively regulated by phosphorylation at Ser9 (Cross et al, 1995), it enhances cell migration via dephosphorylation of focal adhesion kinase (FAK) at Ser722 Bianchi et al, 2005) consistent with our results. Inactivation of PTEN also propagates signaling to proteins further downstream, like S6K on the Akt -Tsc1/2 -mTor -S6K axis.…”
Section: Discussionsupporting
confidence: 91%
“…6a). Activated Akt has been shown to phosphorylate GSK-3 alpha at serine 21 and GSK-3 beta at serine 9 [39]. Phosphorylated GSK-3 exhibits reduced inhibitory activity towards glycogen synthase, thus increasing glycogen synthesis [40].…”
Section: Resultsmentioning
confidence: 99%
“…A number of proteins containing a PH domain are shown to bind phosphatidyl inositol polyphosphates and to be activated by PI3-kinase. These include rac-GEF, unconventional PKCs, Akt/PKB, PDK2 and the Btk family of tyrosine kinases (Franke et al, 1995;Cross et al, 1995;August et al, 1997;Li et al, 1997;Qiu et al, 1998;Ma et al, 1998;Falasca et al, 1998;Van Lint et al, 1998). Much of the attention has recently been focused on Akt as a protector against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the metabolic products of PI3-kinase, phosphatidyl inositol phosphates, bind a protein modular structure, called the pleckstrin-homology (PH) domain . Several PH-domain-containing proteins are found to be e ectors for PI3-kinase (Franke et al, 1995;Cross et al, 1995;August et al, 1997;Li et al, 1997;Qiu et al, 1998). Of particular relevance is Akt/PKB, a serine/ threonine kinase with an N-terminal PH domain, which was recently shown to phosphorylate and inactivate Bad, a protein involved in the apoptosis pathway.…”
Section: Introductionmentioning
confidence: 99%